The challenging role of banks in preventing money laundering and terrorist financing in Latvia - Vītoliņš, Andris (Riga Graduate School of Law, 2021)
One of the main goals of the banking industry is to help detect and deter money laundering and terrorist financing. In this thesis were examined and analyzed the concept of money laundering; the current European and the Republic of Latvia AML legal framework and standards; main procedures and practice aspects of AML in banks in Latvia. The goal of this paper was to find legal imperfections of the European and Latvian AML legal framework and propose theoretical solutions. The resulting research questions to be answered were: how effective is money laundering legislation in Latvia? Do banks, such as AML subjects, effectively fulfil their obligations under the common AML system in Latvia?
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Money laundering; Latvia